Walt Disney's Pinocchio (Danbury, Connecticut : Scholastic, 2006)
Disney's version of the tale by Carlo Collodi of the puppet who is brought to life by a fairy. With the aid of his conscience, Jiminy Cricket, Pinocchio tries to prove himself worthy of becoming a real boy.
Keywords: Children's stories